2011
DOI: 10.1136/bmj.d4366
|View full text |Cite
|
Sign up to set email alerts
|

Moderate dietary sodium restriction added to angiotensin converting enzyme inhibition compared with dual blockade in lowering proteinuria and blood pressure: randomised controlled trial

Abstract: Objective To compare the effects on proteinuria and blood pressure of addition of dietary sodium restriction or angiotensin receptor blockade at maximum dose, or their combination, in patients with non-diabetic nephropathy receiving background treatment with angiotensin converting enzyme (ACE) inhibition at maximum dose.Design Multicentre crossover randomised controlled trial. Setting Outpatient clinics in the Netherlands.Participants 52 patients with non-diabetic nephropathy.Interventions All patients were tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
176
3
9

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 254 publications
(195 citation statements)
references
References 53 publications
7
176
3
9
Order By: Relevance
“…There were several short-term studies on the effect of restricting salt intake on BP and albuminuria reduction during RAAS blockade (6,9,10). Enhanced treatment effects of LSD education on albuminuria were observed in our study.…”
Section: Discussionsupporting
confidence: 51%
See 2 more Smart Citations
“…There were several short-term studies on the effect of restricting salt intake on BP and albuminuria reduction during RAAS blockade (6,9,10). Enhanced treatment effects of LSD education on albuminuria were observed in our study.…”
Section: Discussionsupporting
confidence: 51%
“…Several studies revealed an additive effect of dietary salt restriction with RAAS blockade on BP and proteinuria. However, most of these studies include a small number of patients (6,(9)(10)(11)20), and there has been no randomized, controlled study in Korean populations. Most importantly, the methods for implementing LSDs or high-salt diets used in previous studies offered strongly controlled or modulated diets (6,11), or they provided salt tablets (9), which are not suitable for application in typical clinical practice.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…5 Inhibitors of the renin-angiotensin system (RAS), such as angiotensin-converting enzyme (ACE) inhibitors or angiotensin II receptor blockers (ARBs), are the antihypertensive drugs that most effectively reduce urinary proteins and slow GFR decline in patients with CKD. 1-3, 6 The efficacy of treatment, however, is heterogeneous and dependent on inborn 7 and environmental [8][9][10][11][12] factors. Data in experimental diabetes, 13,14 adriamycin nephrosis, 15 uninephrectomized rats, or in Munich Wistar rats with spontaneously reduced nephron numbers 16 uniformly show that expansion of the sodium pool, with glomerular hyperfiltration and activation of the renal RAS induced by enhanced sodium intake, all contribute to blunt the BP and proteinuria lowering effect of RAS inhibitors.…”
mentioning
confidence: 99%
“…Extracellular volume restriction, by means of moderating dietary sodium intake or concomitant diuretic treatment has been shown to improve the albuminuria‐reducing and blood pressure‐lowering response to RAAS blockade as well as the efficacy of RAAS blockade to decrease cardio‐renal risk 5, 14, 15. The present study shows that NT‐proBNP can help to identify individuals who may not respond to dual RAAS inhibition with aliskiren and who may benefit from diuretic treatment or dietary sodium‐lowering.…”
Section: Discussionmentioning
confidence: 64%